Loss‐of‐function mutation in TSGA10 causes acephalic spermatozoa phenotype in human. Issue 7 (15th May 2020) - Ye, Yuanyuan; Wei, Xiaoli; Sha, Yanwei; Li, Na; Yan, Xiaohong; Cheng, Ling; Qiao, Duanrui; Zhou, Weidong; Wu, Rongfeng; Liu, Qiaobin; Li, Youzhu
Abstract: Background: Acephalic spermatozoa is an extremely rare type of teratozoospermia that is associated with male infertility. Several genes have been reported to be relevant to acephalic spermatozoa. Thus, more genetic pathogenesis needs to be explored. Methods: Whole‐exome sequencing was performed in a patient with acephalic spermatozoa. Then Sanger sequencing was used for validation in the patient and his family. The patient's spermatozoa sample was observed by papanicolaou staining and transmission electron microscopy. Western blot and immunofluorescence were performed to detect the level and localization of related proteins. Results: A novel homozygous frameshift insertion mutation c.545dupT;p.Ala183Serfs*10 in exon 8 of TSGA10 (NM_001349012.1) was identified. Our results showed misarranged mitochondrial sheath and abnormal flagellum in the patient's spermatozoa. TSGA10 failed to be detected in the patient's spermatozoa. However, the expression of SUN5 and PMFBP1 remained unaffected. Conclusion: These results suggest that the novel homozygous frameshift insertion mutation of TSGA10 is a cause of acephalic spermatozoa. Abstract : A novel homozygous frameshift insertion mutation c.545dupT;p.Ala183Serfs*10 in exon 8 of TSGA10 (NM_001349012.1) was identified, which might be the main pathogenesis of the patient with acephalic spermatozoa.